Determination of model potential parameters by fitting the numerical potentials from density functional theory. (30th September 2021) - Zhao, Song-Feng; Wang, Na; Li, Ying-Juan; Guan, Zhong; Wang, Guo-Li; Morishita, Toru; Li, Peng-Cheng
Abstract: Analytical model potentials based on the single-active-electron approximation have been widely used in strong-field physics and attosecond science. In this paper, we determined potential parameters in the Tong–Lin's model potential (Tong and Lin 2005 J. Phys. B: At. Mol. Opt. Phys. 38 2593) for neutral atoms ( Z ⩽ 20), by fitting the numerical potentials calculated from the self-interaction-correction density functional theory and the fitting procedure is performed by the genetic algorithm. The reliability of these potential parameters is carefully examined by comparing the calculated orbital energies with those obtained from the Tong–Lin's parameters and the term averaged experimental energy levels by taking He and Ar atoms for example. We further checked our fitted potential by comparing our calculated high-harmonic-generation and above-threshold-ionization spectra of He and Ar with those from both Tong–Lin's parameters and the Laughlin's model potential (Laughlin and Victor 1988 Adv. At. Mol. Phys. 25 163).